Analisis Faktor Program Promosi, Lokasi Sekolah dan Sarana Prasarana Pendidikan terhadap Minat Peserta Didik Baru (Studi Kasus SMP Gugus Inti 1 Kecamatan Peudada Kabupaten Bireuen) - Anita, Fonna; Win, Konadi; July Saputra, Rudi (peusangan, 2023)
This research, which takes the form of a case study at Gugus Inti-1 Middle School, Peudada District, Bireuen Regency, aims to analyze and examine external factors which are limited to school promotion program factors, school location and educational facilities at the school on the interest of new students at each student admission in that school. The survey was conducted on parents of Class VI students who will enroll their children in the Inti-1 Middle School cluster, namely SMPN 1 Peudada, SMPN 2 Peudada, SMPN 3 Peudada, and SMPN 4 Peudada. This type of associative descriptive research with a quantitative approach. Analytical tool to prove hypotheses through statistical regression analysis models. The research results found that (1) the three factors analyzed, namely school promotion programs, location and educational infrastructure, had a positive effect, both partially and simultaneously, on the interest of new participants in schools in the area studied. (2). The factor that makes the biggest contribution is the location of the school and (3) the large contribution of promotional program factors, school location and educational infrastructure of 42.5% to the interest of new students at SMPN Gugus Inti-1 school, Peudada sub-district, Bireuen Regency.